Levantamiento e implementación de los procesos de negocio académicos en el Área de la Energía, las Industrias y los Recursos Naturales no Renovables de la Universidad Nacional de Loja. - Escaleras Quituizaca, Gabriela Alexandra (2016)
This project describes the techniques and methods for compiling information and academic processes automation of the Energy, Industry and Non-Renewable Natural Resources Department of the National University of Loja, using technologies process management tools and process (BPM). Bearing in mind that process management seeks continuous improvement of processes and for that integrates technological tools and the human resources of the organization. Data collection techniques such as interviews and observations were used, taking into account the statutes and regulations of the university academic system for the identification of business processes. The modeling of processes is based on the BPMN standard and for the automating part BPMS BonitaSoft and ECM Alfresco tools were used for document management. For the four phases of methodology, the Process Management BPM 360º was used, starting with the analysis of the process; followed by the design of the process resulting in the manual of academic processes; then the execution of business processes is the part of automation and finally the monitoring and analysis of processes were performed to find areas for improvement and then to proceed with its implementation.